Hima as a model for neighbourhood open space planning / Khalilah Hassan, Siti Syamimi Omar and Izrahayu Che Hashim - Hassan, Khalilah; Omar, Siti Syamimi; Che Hashim, Izrahayu (2015)
'Hima', which translates as 'protected or preserved place', is a traditional system of resource tenure. It has been practised for over 1400 years in the Arabian Peninsula and is believed to be the most widespread system of traditional conservation in the Middle East, and perhaps the entire earth. They have secured sustainable use of renewable natural resources by and for the people living adjacent to them. Thus 'hima' has been one of the most successful institutions integrating nature conservation with human wellbeing. In these modern times, environmental protection is a new concept which has emerged in response to modern problems linked to industrialisation and globalisation. In reality, the need to protect the environment from abuse has been a constant concern for humans since the beginning of time- especially for people who were living directly of the earth's resources. Poor land management and man's greed in getting instant wealth have been identified as amongst the reasons that contribute to the degradation of environmental quality, especially that which relates directly to land. The aims of this paper are to highlight the concept and characteristics of the hima in spatial planning and management and how it can be allocated in neighbourhood areas. A neighbourhood area of Kota Bharu, Kelantan has been used as a study area for mapping the potential hima.